1973
DOI: 10.1139/b73-266
|View full text |Cite
|
Sign up to set email alerts
|

Isoperoxidases of (IAA oxidase) oxidase in oat coleoptiles

Abstract: Eight constitutive isoperoxidases were separated by the disc method of polyacrylamide gel electrophoresis from a lyophilized extract of 8-day-old oat (Avena sativa L., cv. Victory) coleoptiles. Both anodic and cathodic isoperoxidases were studied and differences in electrophoretic mobilities and hydrogen donor substrate specificities were revealed. In addition, by enzyme assay, cathodic and anodic isoenzymes were shown to possess differences in peroxidase and IAA (indole-3-acetic acid) oxidase activities.Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The reduction in peroxidase activity by exogenously applied IAA has been reported in several plant systems (Gordon and Henderson 1973, Morrow and Jones 1986, Ockerse et al 1965, Ockerse and Mumford 1973, Ros Barceló et al 1989), but only a few reports describe the effect of this auxin on peroxidases from the cell walls (Morrow andJones 1986, Ros Barceló et al 1989). In pea internode sections, intercellular peroxidase activity was decreased by IAA treatment, an effect that correlated inversely with the elongation rate (Morrow and Jones 1986), and application of IAA or 2,4 dichlorophenoxiacetic acid to exponentially growing lupin hypocotyls promoted a reduction in the level of free intercellular peroxidases (Ros Barceló et al 1989).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reduction in peroxidase activity by exogenously applied IAA has been reported in several plant systems (Gordon and Henderson 1973, Morrow and Jones 1986, Ockerse et al 1965, Ockerse and Mumford 1973, Ros Barceló et al 1989), but only a few reports describe the effect of this auxin on peroxidases from the cell walls (Morrow andJones 1986, Ros Barceló et al 1989). In pea internode sections, intercellular peroxidase activity was decreased by IAA treatment, an effect that correlated inversely with the elongation rate (Morrow and Jones 1986), and application of IAA or 2,4 dichlorophenoxiacetic acid to exponentially growing lupin hypocotyls promoted a reduction in the level of free intercellular peroxidases (Ros Barceló et al 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Catabolism of IAA through oxidation has been demonstrated to be catalyzed by peroxidases in active growing tissues (Gordon and Henderson 1973, Ockerse and Mumford 1973). Several studies indicated that IAA decreased peroxidase activity in plant tissues in which this auxin induces cell elongation (Morrow and Jones 1986, Ockerse and Mumford 1973, Ros Barceló et al 1989).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Significant differences in the manner and degree of influence on the activity of basic peroxidases between growth regulators tested and CHF were observed. It is well known that these enzymes function as IAA-oxidases as well (Gordon and Henderson 1973) and participated in the cessation of plant growth. Recently Quiroga et al (2001) have shown that basic peroxidases function in the lignification too.…”
Section: Discussionmentioning
confidence: 99%